Temperature seasonality and ENSO variability in the northern South China Sea during the Medieval Climate Anomaly interval derived from the Sr/Ca ratios of Tridacna shell. (15th August 2019) - Liu, Chengcheng; Yan, Hong; Fei, Haobai; Ma, Xiaolin; Zhang, Wenchao; Shi, Ge; Soon, Willie; Dodson, John; An, Zhisheng
Graphical abstract: Highlights: A 30-year long monthly SST record during MCA was obtained from a Tridacna shell. The seasonality of SST during MCA was smaller than that of recent decades. The frequency of ENSO activity during MCA was similar to that of recent decades. Abstract: The nature of how the El Niño–Southern Oscillation (ENSO) and its seasonality respond to warmer climate is critical knowledge to predict future climates under the expected anthropogenic warming scenario. In this study, a sub-fossil Tridacna gigas specimen was collected from the northern SCS and AMS 14 C dating suggested that the animal lived around AD 1099, during the Medieval Climate Anomaly (MCA) interval, the most recent natural warm period of the late Holocene. Monthly Sr/Ca ratios were determined by the ICP-OES measurements and a 30-year long SST record was calculated based on a Sr/Ca-SST calibration equation. The results showed that the SST seasonality for this 30-year window around AD 1099 was about 3.11 °C, which is smaller than the modern warm period (i.e., about 4.36 °C for AD 1994 ∼ 2005 interval). This new result is consistent with another published Tridacna gigas record that was dated around AD 990 from the northern SCS. The signals of ENSO activity were also extracted from the reconstructed SST record and statistical analyses yielded 9 El Niño events and 8 La Niña events within the 30-year record, indicating that the frequency of ENSO activity around AD 1099 was similar to the modern instrumental period.